(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2019)
The dried leaves of Ilex paraguariensis, also known as yerba mate or chimarrão, are used to produce infusions consumed by over 1 million people worldwide, being a traditional drink in several South American countries, particularly, Argentina, Brazil, Uruguay, and Paraguay. The positive effects of I. paraguariensis in obesity have been described and observed in some clinical trials both in animals and in humans. The main goal of this work was to perform a systematic review, complying with the PRISMA (Preferred Reported Items for Systematic Reviews and Meta-Analysis) recommendations, followed by a meta-analysis and Trial Sequential Analysis (TSA), to summarize the results of the recent clinical trials, clarifying the anti-obesity potential of I. paraguariensis. The search for this systematic review was performed on several electronic databases (Pubmed, Web of Science, Scopus, SciELO and Cochrane Library) in July 2017. A total of 22 clinical trials were considered for the quantitative synthesis of the data, totalizing 726 patients enrolled. In conclusion, this systematic review demonstrated the positive effects of I. paraguariensis consumption on the reduction of body weight, body mass index (BMI), and waist circumference of patients, showing its anti-obesity potential.